LO014: What ultrasonography characteristics predict surgical intervention for testicular torsion in adults?. (2nd June 2016) - Ritcey, B.W.; Woo, M.; McInnes, M.D.; Watterson, J.; Perry, J.J.
Abstract : Introduction: Testicular torsion is a time sensitive condition for which there can be significant delays to surgery or transfer to definitive care while trying to obtain an ultrasound to confirm the diagnosis. This study determines the test characteristics for each individual sonographic sign of testicular torsion associated with the patient requiring surgical intervention.Methods: A retrospective health records review of adult patients with acute, non-traumatic scrotal pain or swelling (defined as under 24 hours since onset) presenting to one of two Canadian academic tertiary care emergency departments between November 2009 and March 2013 was performed. A single data abstractor completed a case report form for each patient including demographics, individual ultrasound findings, final diagnosis, and need for surgical intervention. The sensitivity and specificity of each ultrasonographic sign (including testicular heterogeneity, decreased colour doppler, and decreased pulsed wave doppler) at predicting surgical intervention during the same hospital visit was calculated along with 95% confidence intervals.Results: During the study period there were a total of 876 emergency department visits for scrotal pain, of which 198 patients met our inclusion criteria. The included patients had a mean age of 36.2 years. Decreased blood flow to the painful testicle on colour doppler showed the best overall test characteristics with a sensitivity of 82.4% (95% CI 55.8%-95.3%) and specificity of 100% (95% CI 96.3%-100%) for predicting a need for surgical intervention for testicular torsion. Other ultrasound findings for testicular torsion included a heterogeneous appearance of the painful testicle (sensitivity 47.1% [95% CI 23.9%-71.5%], specificity 77.4% [95% CI 68.9%-84.2%]), and decreased arterial or venous flow on pulsed wave doppler (sensitivity 76.5% [95% CI 49.8%-92.1%], specificity 100% [95% CI 96.3%-100%]).Conclusion: Decreased blood flow to the painful testicle on colour doppler showed excellent specificity and can rapidly "rule-in" a need for surgical intervention for testicular torsion. Given that colour doppler is relatively easy to learn and perform, future studies should assess the use of colour doppler using point of care ultrasound to expedite surgical consultation.